Changes in soil organic carbon in native forests of Argentina related to land use change and environmental factors - Nosetto, Marcelo Daniel; Balducci, Ezequiel Diego; Gaitan, Juan Jose; Mastrangelo, Matias Enrique; Martínez Pastur, Guillermo José; Pinazo, Martin Alcides; Villagra, Pablo Eugenio; Gonzalez Roglich, Mariano; Kowaljow, Esteban; Colazo, Juan Cruz; Perez Harguindeguy, Natalia; Naldini, María Betania; et al. (Wiley, 2024)
Native forests host important pools of soil organic carbon (SOC). This is a key element not only for ecosystem functioning but also for the global carbon cycle. Globally, and particularly in Argentina, native forests are being rapidly replaced by other land uses, raising questions about the impact of these transformations on SOC and its environmental controls. Based on the construction of the largest SOC database in Argentina to date, we investigated the patterns and controls of changes in SOC stocks associated with the replacement of native forests by other land uses. We constructed the database with a total of 818 sites with SOC data (0–30 cm depth), covering the main ecoregions, to which we added environmental information (e.g. satellite data, soil database and climate database), to study the environmental controls on SOC change after deforestation and on the original SOC content of native forests. Considering all ecoregions and all land use alternatives together, we found an average decrease in SOC stock of 18.2 Mg C ha−1, which represents a loss of more than a quarter of the original SOC stock of the native forest sites. A boosted regression tree explained 89% of the variation in SOC stock change and indicated that the initial forest SOC stock and the post-deforestation land use were the most important variables explaining this variation (relative influence of 30.9% and 18.2%, respectively). The replacement of native forests by rainfed annual crops resulted in the largest decrease in SOC (−28 Mg C ha−1), which was twice as large as the decrease observed in rangelands (−14 Mg C ha−1). On the contrary, neither irrigated croplands nor tree plantations of fast-growing species caused a decrease in SOC stocks (p > .10). Climate and soil texture had an indirect effect on SOC changes through a strong influence on the initial SOC stocks in native forests (p < .01). Our study highlighted the significant impact of land use change on SOC stocks, overshadowing other relevant environmental controls. Understanding how the SOC pool responds to land use change, environmental conditions and management practices is essential to increase the effectiveness of practices implemented to improve soil properties and mitigate climate change.